2014
DOI: 10.2478/s11658-014-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of gene expression in ABCC6 knockdown HepG2 cells

Abstract: ABCC6 protein is an ATP-dependent transporter that is mainly found in the basolateral plasma membrane of hepatocytes. ABCC6 deficiency is the primary cause of several forms of ectopic mineralization syndrome. Mutations in the human ABCC6 gene cause pseudoxanthoma elasticum (PXE), an autosomal recessive disease characterized by ectopic calcification of the elastic fibers in dermal, ocular and vascular tissues. Mutations in the mouse ABCC6 gene were also associated with dystrophic cardiac calcification. Reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 26 publications
(31 reference statements)
3
49
0
Order By: Relevance
“…We performed all experiments in stable ABCC6 knockdown HepG2 cells that had been previously generated and studied [20]. Unexpectedly, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed all experiments in stable ABCC6 knockdown HepG2 cells that had been previously generated and studied [20]. Unexpectedly, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…delivery. Indeed, ABCC6 knockdown causes an increase of TNAP in an in vitro model, 42 and there was a possibility that this could also happen in vivo and affect PPi clearance in mice. We found that a 112 mmol/kg (50 mg/kg) injection produced after 5 minutes a plasma concentration of approximately 14 mmol/L, which corresponds to a bioavailability of approximately 0.5%.…”
Section: Ppi Administrationmentioning
confidence: 99%
“…Considering the inheritable calcification syndromes resulting from dysfunctional ABCC6, this transporter is now viewed as a key player in ectopic mineralization pathologies, but it is unclear how ABCC6 contributes to this process. Nonetheless, the latest studies indicate that loss of ABCC6 alters gene expression profiles in a way that mineralization-promoting genes (tissue-nonspecific alkaline phosphatase ( TNAP ), bone morphogenetic protein ( BMP )) are upregulated while the expression of genes with the opposite effect (ecto-5′-nucleotidase ( NT5E ), Fetuin A and Osteopontin ) is decreased both in vitro [ 81 ] and in vivo [ 82 ]. Moreover, recent in silico studies have suggested new substrate candidates for ABCC6 that hopefully will be evaluated experimentally in vitro and in vivo in the near future [ 83 ].…”
Section: Abc Transporters In the Regulation Of Endothelial Functiomentioning
confidence: 99%